Implementation of a P&E management system for a dual-source EV powered by different batteries - Thakre, Mohan P.; C. Tapre, Pawan; Somnath Kadlag, Sunil; Prakash Kadam, Deepak; S. Thorat, Jayawant; N. Nandeshwar, Rahul; S. Gaikwad, Rohit (Bulletin of Electrical Engineering and Informatics, 2023)
There is an era started in the field of power energy (PE) management in the electric vehicles (EVs) application cloud, which impacts the smart grid in significant ways and necessitates the collaboration of multiple branches of engineering. Most of the problems with EVs stem from their limited range, which can be improved by incorporating additional forms of energy storage. This paper makes an effort to bring a fresh viewpoint to the description of the power and energy management problem facing EV, taking into account all the needs of such a vehicle. Using a novel power and energy management system, the proposed methodology enables a systematic approach to this multidisciplinary problem. Implementing a power and energy management system for a dual-source EV using lead-acid batteries and ultra-capacitors (UCs) exemplifies the novel framework's capabilities. The electronic power development architecture is outlined in detail, along with the implementing modular blocks that make up the entire system architecture.